The Relationship Between Breathing Relaxation and Pain Intensity During the First Stage of Labor in the Working Area of UPT Puskesmas Watampone in 2023 - Ismawati Ismawati; Rahmiati Rahmiati; Andi Nurul Azizah; Nursuciyani Jamal; Rahmawati Rahmawati (PT. Global Research Collaboration, 2026)
Labor pain is a physiological condition commonly experienced during the first stage of labor due to uterine contractions and cervical dilation. This condition may increase sympathetic nervous system activity and affect maternal comfort. Effective pain management is needed, and breathing relaxation is a simple non-pharmacological technique that may help reduce pain intensity through controlled breathing and improved oxygenation. This study aimed to analyze the effect of breathing relaxation on pain intensity during the first stage of labor using a quasi-experimental pretest-posttest design without a control group. The sample was selected using purposive sampling with inclusion criteria of women aged 20–39 years in the first stage of labor. Pain intensity was measured using a Numerical Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon test. The results showed a significant reduction in pain intensity after the intervention (p = 0.001), indicating that breathing relaxation has a significant effect on reducing labor pain intensity.